2019
DOI: 10.1111/dth.12860
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in two patients with pemphigus vulgaris under multiagent immunosuppressive drug therapy: A rare entity to remember in the differential diagnosis of fever of unknown origin

Abstract: Pemphigus vulgaris (PV) is an autoimmune blistering skin disease that may require multiagent immunosuppressive drug therapies in severe cases. In addition to the well‐established corticosteroid sparing agents azathioprine, mycophenolate mofetil, and methotrexate, rituximab is being increasingly used alone or in combination in the management of PV. Due to the chronic course of the disease, the cumulative effects of these therapy agents over long follow‐up periods may result in various adverse reactions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…However, to date, there is no known radical cure for the disease: symptoms are only relieved with scientific treatment [8]. Sole treatment with prednisone produces unsatisfactory results, which do not meet expected clinical outcomes [9]. Studies have revealed that the incorporation of immunosuppressive therapy effectively improved treatment results in patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there is no known radical cure for the disease: symptoms are only relieved with scientific treatment [8]. Sole treatment with prednisone produces unsatisfactory results, which do not meet expected clinical outcomes [9]. Studies have revealed that the incorporation of immunosuppressive therapy effectively improved treatment results in patients.…”
Section: Introductionmentioning
confidence: 99%